2007
DOI: 10.1158/1078-0432.ccr-06-2492
|View full text |Cite
|
Sign up to set email alerts
|

Relaxin Promotes Prostate Cancer Progression

Abstract: Purpose:To understand the role of relaxin peptide in prostate cancer, we analyzed the expression of relaxin and its receptor in human prostate cancer samples, the effects of relaxin signaling on cancer cell phenotype in vitro, and the effects of increased serum relaxin concentrations on cancer progression in vivo. Experimental Design: The relaxin and its receptor leucine-rich repeat containing G proteinĉ oupled receptor 7 (LGR7) expression were studied by quantitative reverse transcription-PCR (11 benign and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
102
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(111 citation statements)
references
References 35 publications
(47 reference statements)
8
102
0
1
Order By: Relevance
“…In this study, it was observed that relaxin 2 improved maintenance of cellular viability and proliferation of both the LNCaP and PC3 prostate cancer cell lines. These results confirm earlier studies showing that this peptide hormone promotes the division of prostate cancer cells (6). Experimental studies report that greater changes of cell proliferation take place in the high AR expression cells (LNCaP) than low AR (B) The change in the level of MMP-2 and MMP-9 secretion determined by the gelatin zymography assay.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In this study, it was observed that relaxin 2 improved maintenance of cellular viability and proliferation of both the LNCaP and PC3 prostate cancer cell lines. These results confirm earlier studies showing that this peptide hormone promotes the division of prostate cancer cells (6). Experimental studies report that greater changes of cell proliferation take place in the high AR expression cells (LNCaP) than low AR (B) The change in the level of MMP-2 and MMP-9 secretion determined by the gelatin zymography assay.…”
Section: Discussionsupporting
confidence: 89%
“…The peptides were used at a final concentration of 10 -8 M for all experiments. This concentration was selected on the basis of earlier research work and trial experiments (6). The medium, FBS and other culture supplements / reagents were purchased from Gibco (Thermo Fisher scientific, Inc.) unless otherwise specified.…”
Section: Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, androgen withdrawal-induced marked downregulation of relaxin, VEGF, vimentin and BMP-6, involved in cancer progression (Soker et al, 2001;Dai et al, 2005;Thompson et al, 2006;Feng et al, 2007;Wei et al, 2008) as well as upregulation of cellular retinol binding protein 7 and interferon-g receptor, negatively regulating cancer progression (Kuppumbatti et al, 2001;Yang et al, 2008), in LNCaP/IL-6#1. In addition, DnaJ, acting as a cytoprotective chaperon in response to stress-induced apoptosis (Cajo et al, 2006), were upregulated in LNCaP/IL-6#1, which might be an adaptive change as observed in Akt and MAPK pathways after androgen deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, expression levels of some genes associated with the progression of prostate cancer, such as relaxin, vascular endothelial growth factor (VEGF), vimentin and bone morphogenetic protein-6 (BMP-6) (Soker et al, 2001;Dai et al, 2005;Thompson et al, 2006;Feng et al, 2007;Wei et al, 2008), were significantly downregulated in LNCaP/IL-6#1 compared with LNCaP/Co. Overall, there are several genes listed in Table 1, which are known to have functions mediating cell growth, apoptotsis, and tumorigenesis, showing expression profiles that are reasonable for theoretically elucidating the molecular mechanism mediating enhanced sensitivity to androgen withdrawal by overexpression of IL-6.…”
Section: Effects Of Interleukin-6 Secretion On Prostate Cancer T Teramentioning
confidence: 99%